Stakeholder Management: An Insightful Overview of Issues - Mashali, Ayman; Elbeltagi, Emad; Motawa, Ibrahim; Elshikh, Mohamed (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
This paper attempts to contribute towards investigating the existing literature base of stakeholder management (SM), provide a compilation, and define any gaps in this area. Besides, explore different groups of critical success factors (CSFs) and grouping these actors. This study is based on reviewing the literature. Therefore, more than a hundred research papers were searched by the key terms specified in a preceding literature review. Succeeding tours of abstract research surveys resulted in forty-two research papers being picked for the compilation. SM constructs were identified, and the following crucial analysis defined the literature base gaps. The most notable outcomes are the absence of research that has studied BIM-based stakeholder management, especially in mega projects. Additionally, further investigations are still required to study the SM influence throughout the different stages of the project life cycle and study the impact of project type and contract type in SM. However, there is still considerable debate about the SM nature and merits approach. This study presents a comprehensive gathering of all earlier identified SM processes through a structured approach. Additionally, a more realistic and practical methodology for the development and implementation of SM will emerge, and twenty-seven CSFs associated with SM in construction projects are identified. The study is expected to have a theoretical contribution to this subject, especially in the context of the Qatari construction industry.